Residência Pedagógica e bullying: Relato de experiência com alunos do ensino fundamental I. - Roque, Estefanny Pinto (Brasil, 2022)
This experience report aims to present the pedagogical activities of intervention about bullying in schools. These activities were applied with students from the 5th grade of elementary school I, during the return to classes 100% on site, in the Pedagogical Residency Program, promoted by the Coordination for the Improvement of Higher Education Personnel (CAPES). Through the subproject of Physical Education, I was part of a team of students from the Faculty of Physical Education and Physiotherapy - FEFF, from the Federal University of Amazonas - UFAM, which was assigned to the Professora Gelcy Sena Abrantes Municipal School, located in the neighborhood of Redenção, Manaus-AM. This report consists of describing the experiences and strategies adopted at school during the campaign "Orange March: Everyone against bullying" promoted by the school. Two activities were applied in order to make students aware of the type of violence that occurs in schools, called "Bullying". The activities were developed in a satisfactory way, bringing good feedback both from the students, who showed a lot of interest, and from the preceptor who was observing and recording the class. The teacher in the classroom is the highest authority figure, therefore his interventions are necessary to combat bullying in schools.